Modeling of social risks in the labor sphere - Olha Shulha; Tatiana Kostyshyna; Maryna Semykina; Liudmyla Katan; Hanna Smirnova (Journal of Risk and Financial Management, 2021)
Modern society has developed in such a way that social reality is characterized by the significant dynamics of all processes and their uncertainty. Under such conditions, risk accompanies any purposeful activity of the social subject, and, in turn, the latter is aimed at reducing the uncertainty of its results. The purpose of this paper is to form the basis of a comprehensive study of social risks in the labor sphere and to develop practical recommendations for minimizing their negative consequences. In order to determine the main factors influencing the probability for the unemployed not to work in the specialty in which they have trained, we used the data of a micro-level survey on economic activity of the population to build linear regression models based on structural variables. As a result of applying the method of economic-mathematical modeling, in particular the basics of probability theory, the models of social risks of unemployment in terms of occupational groups and employment of unemployed persons outside of the specialty they have trained in were developed. The models developed made it possible to formalize and identify patterns of supply and demand dynamics of labor in terms of professions, as well as to identify the main factors influencing the change in the probabilistic characteristics of employment of unemployed persons outside of the specialty they have trained in.
Keywords: 330; social risks; labor sphere; unemployment; modeling; management